(untitled) - Norris, Jay (New York, 2010)
Mastering the Currency Market is a comprehensive guide to currency and futures trading strategies and techniques for both highly volatile and nonvolatile markets. Putting to work their vast and highly diverse experience in forex trading, the authors explain how to take advantage of the many benefits of foreign exchange trading, including its low cost of entry afforded by margin, and the dynamic pricing by nature of the competitive marketplace.
Keywords: Foreign exchange market,Thị trường ngoại hối